Geoestadistica multivariante aplicada a estudios regionales de evapotranspiracion - Martinez-Cob, A.=700 1 Cuenca, R.H.; Faci, J.M.
(Es, En)
ilus., 21 ref.
Keywords: GEOLOGIA; METODOS ESTADISTICOS; EVAPOTRANSPIRACION; ESPAÑA; GEOESTADISTICA; KRIGEADO; COKRIGEADO; ELEVACION